Negotiating Discourse: Towards adopting a content-based approach to academic literacy courses - Drennan, Laura Maria (South African Journal of Higher Education, 2016)
A study was conducted on the extent to which a particular academic literacy course addressed the literacy needs of students enrolled in a foundational developmental programme at a South African university. Various factors influencing student motivation for the course were identified. The findings suggest that students do not want to engage in course materials they considered irrelevant and uninteresting, which impacted on the value they assign to the course in general. Furthermore, students also indicated that they were unsure of what was expected of them in terms of assessment in the course. In response to the findings of the study, a more content-based instruction (CBI) approach to the literacy courses was taken at the university. The article explores the extent to which a content-based approach could, in theory, address some of the issues pertaining to student motivation for academic literacy courses in a South African higher-education context.